2012
DOI: 10.1007/s10029-012-0933-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient perception of laparoscopic versus open mesh repair of inguinal hernia, the hard sell

Abstract: The results show that many patients have an incorrect perception of laparoscopic inguinal hernia repair, which may reflect an inadequate consent and counselling process. No definitive evidence exists regarding the superior safety and efficacy of one method over another, but it would appear that a significant number of patients are unaware of this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In experienced hands, laparoscopic inguinal hernia repair is also safe although unquestionably associated with a higher risk of rare but "serious" complications, and even death following an elective operation [26,28]. Furthermore, it is evident that patient perceptions of the pros and cons of open and laparoscopic methods are often incorrect suggesting an inadequate consent and information process by the treating surgeon [32]. In relation to long-term problems, patients offered the laparoscopic approach are not routinely warned about the risk of scarring from placement of mesh in the pelvis which might compromise future oncological surgery [33][34][35].…”
Section: Comparison Of Polypropylene Mesh Vs Parietex Progrip Tm Meshmentioning
confidence: 99%
“…In experienced hands, laparoscopic inguinal hernia repair is also safe although unquestionably associated with a higher risk of rare but "serious" complications, and even death following an elective operation [26,28]. Furthermore, it is evident that patient perceptions of the pros and cons of open and laparoscopic methods are often incorrect suggesting an inadequate consent and information process by the treating surgeon [32]. In relation to long-term problems, patients offered the laparoscopic approach are not routinely warned about the risk of scarring from placement of mesh in the pelvis which might compromise future oncological surgery [33][34][35].…”
Section: Comparison Of Polypropylene Mesh Vs Parietex Progrip Tm Meshmentioning
confidence: 99%
“…Even when complications have been discussed and documented, patient recalling and understanding can be affected [18]. Notably patients misunderstand the relative risks and benefits of laparoscopic versus open IHR even after counselling [19]. Furthermore, one study has shown that there are inconsistencies between documentation and what is actually discussed with the patient [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding in Patel et al's study is that most patients arrive at an outpatient appointment without a preferred method and possibly directed to laparoscopic repair, reflecting surgical practice of the institution [10]. Most surgeons have their own strong views and preferences over one repair technique, and can convince their patients in favor of an approach.…”
mentioning
confidence: 98%
“…Generally, surgeons tell their patients that ELR's are less invasive and related with less pain and quicker recovery. In a very recent questionnaire study about the patient perception of laparoscopic versus open mesh repairs, it was revealed that many patients had incorrect perceptions, a large number were under the false impression that laparoscopic techniques were safer, quicker and less likely to recurrence over open repair [10]. Besides, many patients felt that laparoscopic repair was the only method which could be undertaken as a day case procedure.…”
mentioning
confidence: 99%